The Immune Response and Immunopathology of COVID-19 - Mortaz, Esmaeil; Tabarsi, Payam; Varahram, Mohammad; Folkerts, Gert; Adcock, Ian M. (Frontiers in Immunology, 2020)
Coronaviruses were first discovered in the 1960s and are named due to their crown-like shape. Sometimes, but not often, a coronavirus can infect both animals and humans. An acute respiratory disease, caused by a novel coronavirus (severe acute respiratory syndrome coronavirus-2 or SARS-CoV-2 previously known as 2019-nCoV) was identified as the cause of coronavirus disease 2019 (COVID-19) as it spread throughout China and subsequently across the globe. As of 1 May 2020, a total of 3,383,501confirmed cases globally, with 238,587 deaths had been reported by WHO. SARS-CoV-2 belongs to the β-coronavirus family and shares extensive genomic identity with bat coronavirus suggesting that bats are the natural host. SARS-CoV-2 uses the same receptor, angiotensin-converting enzyme 2 (ACE2), as that for SARS-CoV, the coronavirus associated with the SARS outbreak in 2003. It mainly spreads through the respiratory tract with lymphopenia and cytokine storms present in the blood of subjects with severe disease. This suggests the existence of immunological dysregulation as an accompanying event during severe illness caused by this virus. The early recognition of this immunological phenotype could assist prompt recognition of patients who will progress to severe disease. Here we review the data of the immune response during COVID-19.